Cytogenetic discrepancy between uncultured amniocytes and cultured amniocytes in mosaic trisomy 18 at amniocentesis in a pregnancy with a favorable fetal outcome and maternal uniparental disomy 18 - Chih-Ping Chen; Jun-Wei Su; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Wen-Lin Chen; Meng-Shan Lee; Chen-Wen Pan; Yun-Yi Chen; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis of mosaic trisomy 18 in a pregnancy with a favorable fetal outcome and maternal uniparental disomy 18. Case report: A 38-year-old, primigravid woman underwent the first amniocentesis at 16 weeks of gestation because advanced maternal age. Amniocentesis revealed a karyotype of 46,XX [22/22] in cultured amniocytes, and 36% mosaicism for trisomy 18 and a maternally inherited Xp22.31 microdeletion by array comparative genomic hybridization (aCGH) in uncultured amniocytes. The second amniocentesis at 18 weeks of gestation revealed 47,XX,+18 [14]/46,XX [36] in cultured amniocytes and 36% mosaicism for trisomy 18 by multiplex ligation-dependent probe amplification (MLPA) P095 in cultured amniocytes. Prenatal ultrasound was normal. The parents were phenotypically normal. The third amniocentesis at 23 weeks of gestation revealed 47,XX,+18 [3]/46,XX [17] in cultured amniocytes, and in uncultured amniocytes, aCGH revealed 45%-50% mosaicism for trisomy 18, interphase fluorescence in situ hybridization (FISH) revealed 36% (36/100 cells) mosaicism for trisomy 18, and quantitative fluorescent polymerase chain reaction (QF-PCR) showed mosaic maternal uniparental heterodisomy for chromosome 18 and mosaic trisomy 18 of maternal origin. The fourth amniocentesis at 32 weeks of gestation revealed a karyotype of 46,XX [20/20] in cultured amniocytes, and in uncultured amniocytes, aCGH revealed 50%-60% mosaicism for trisomy 18, FISH revealed 21.8% (22/101 cells) mosaicism for trisomy 18, and non-invasive prenatal testing (NIPT) showed chromosome 18 gene dosage increase in the maternal blood. At 34 weeks of gestation, a 1480-g phenotypically normal baby was delivered. The cord blood had 47,XX,+18 [10]/46,XX [30]. The umbilical cord had 47,XX,+18 [4]/46,XX [36]. The placenta had 47,XX,+18 [40/40], and QF-PCR analysis confirmed trisomy 18 of maternal origin. When follow-up at age four months, the neonate was phenotypically normal, FISH analysis on buccal mucosal cells revealed 2% (2/100 cells) mosaicism for trisomy 18, and the peripheral blood had 47,XX,+18 [18]/46,XX [22]. When follow-up at age eight months, the neonate had normal development, the peripheral blood had 47,XX,+18 [15]/46,XX [25], and the buccal mucosal cells showed maternal uniparental heterodisomy for chromosome 18. Conclusion: Cytogenetic discrepancy may occur between uncultured and cultured amniocytes in mosaic trisomy 18 at amniocentesis. Cultured amniocytes may present progressive decrease in the levels of mosaicism for trisomy 18 as the fetus grows. Mosaic trisomy 18 at amniocentesis can be associated with a favorable outcome.